In vitro culture establishment from Cotyledon and Embryonic Axis Explants of two Bangladeshi Sunflower (Helianthus annus L.) varieties - Chowdhury, Maisha Mosharrat (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2015.